An Investment Analysis on Business Strategy Simulation to improve Bio Ethanol Price Competitiveness using Simple Multi Single Step Reactor Cellulose Ethanol - Setiawan, Achmad; Siahaan, Uke (The Indonesian Journal of Business Administration, 2014)
Abstract. As the main fuel source became depleted, studying or evaluating on alternative fuel source became more serious.  Ethanol as one of this alternative fuel becomes ever more feasible. PT. Pupuk Kujang smell this opportunity, by using government initiative they tried developing starch technology in Cikumpay - Purwakarta.  Bearing sad tiding the starch technology had it inherit drawback one of them are Food or Fuel dilemma. This problem can be adverted by optimizing ethanol business through cellulose bio ethanol which relied on waste bio mass instead of food source.  This cellulose technology still poses its own drawback which is production inefficiency, since the bio mass to ethanol conversion rate are lower than starch it required huge amount of bio mass.  Down scaling the plant to a manageable level, and creating higher probability of successful conversion through plant and bio reactor portfolio, cellulose technology can be brought to a more optimal production level thus opening new windows of opportunity. Further plant operation management optimization can be achieved, through changing energy source from full bio mass to solar energy.  Plotting the plant location within market place can be done through splitting the distillation process from bio reactor process. This also creates more effective transportation since one way trip is possible from the market place to distillation complex.  Lowering grade produce within the reactor also increase safety and further ease plan operation. Through the right strategic approach, and acting as PT. Pupuk Kujang SBU as waste bio mass and ethanol provider, this project could be executed in field operation, without worrying of this plant inherit flaw.  Through financial analysis this project passes for great investing prospect with ROI at 186% and IRR at 32%.  Sensitivity test also prove that investor should be more focus on productivity than environment aspect since only 20% impairment of productivity can bring this plant to a loss condition.